2000
DOI: 10.1177/107110070002100704
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Mobilization in the Healing of Achilles Tendon Repair

Abstract: Twenty-four male New Zealand rabbits underwent suture repair of a tenotomy of the left achilles tendon. The rabbits were randomized into two groups of 12 animals; in group (A), the ankle was immobilized by pinning for 35 days, while in the group (B), the ankle was immobilized for only 14 days followed by active mobilization. Following sacrifice at 35 days postoperatively, the retrieved tendons were evaluated by biomechanical testing and histologic examination. Approximately 50% of stretching occurred in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 33 publications
2
57
1
3
Order By: Relevance
“…Under loading conditions, cells within the ligament sense tissue strains and respond by modifying the tissue. Mobilization for the treatment of soft tissue damage has also been found to decrease muscle atrophy, osteoporosis, adhesions, and joint stiffness following injury [125][126][127][128][129][130][131]. According to a review by Hurley and Roth, studies have indicated that, even in healthy and diseased older adults, short-term high-intensity strength training is well tolerated and helps reduce proinflammatory cytokines and knee joint loads.…”
Section: Mobilization and Exercisementioning
confidence: 99%
“…Under loading conditions, cells within the ligament sense tissue strains and respond by modifying the tissue. Mobilization for the treatment of soft tissue damage has also been found to decrease muscle atrophy, osteoporosis, adhesions, and joint stiffness following injury [125][126][127][128][129][130][131]. According to a review by Hurley and Roth, studies have indicated that, even in healthy and diseased older adults, short-term high-intensity strength training is well tolerated and helps reduce proinflammatory cytokines and knee joint loads.…”
Section: Mobilization and Exercisementioning
confidence: 99%
“…4,8,10,23 Hypoxiaand mechanically induced degenerative changes can arise from this behavior; histologic findings 5,6,10 have demonstrated that spontaneous AT ruptures occur in these patients, with nonuniform distribution of stress resulting in vascular injury due to ischemic torque placed on the AT. Therefore, in addition to an adequate postoperative intervention plan, these patients require lessons in appropriate techniques for sport reintegration and regular sport practice.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6,15,22 However, most treatments include recommendations for primary reattachment of the damaged ends to achieve appropriate mechanical stability, a percutaneous approach to avoid excessive tissue damage, 1,2,4,8 and early rehabilitation 3,5,6,8,10,16,[21][22][23] to promote better clinical outcomes than are typical with open or traditional rehabilitation programs. 3,5,6,8,10,16,22,23 Traditional models do not appear to provide the tissue and neuromuscular benefits that early models provide. 3,6,10,16,[21][22][23] Indeed, they result in pathologic adaptations to plantar-flexion tasks.…”
mentioning
confidence: 99%
See 2 more Smart Citations